P118 Patient perceptions of physical activity in systemic lupus erythematosus – an explorative qualitative study. (23rd March 2020) - Keith-Jopp, Chloe; Coxon, Kirstie; Nikoletou, Dimitra; Morrissey, Dylan; Pyne, Debasish
Abstract : Background: Physical Activity (PA) promotion is a global health priority, with a positive impact on fatigue, pain and cardiovascular disease risk for People with Systemic Lupus Erythematosus (PwSLE). Nonetheless, PwSLE typically appear to lead sedentary lives with low adherence to PA programmes. We aimed to inform PA promotion efforts for this group by exploring perceptions of PA in PwSLE. Methods: This qualitative study employed a constructivist framework with meaningful patient and public involvement at all stages from design to dissemination. Ten PwSLE at a tertiary Lupus Centre participated in semi-structured interviews, which were audio-recorded and transcribed verbatim to enable thematic analysis. Rigour and trustworthiness of findings was ensured through field notes and multiple coding. An independent patient lupus group discussed the findings to provide respondent validation and further context. Results: Eight themes (figure 1 ) emerged from the interview data including four inductive themes related to PwSLE experience of SLE; diagnosis with an unknown disease, knowledge of SLE, lost identity and self-management strategies. These themes were precursors to four deductive themes; benefits of PA, barriers to PA, facilitators to PA and manageable PA. PwSLE experience of the condition underpinned their perceptions of PA. Conclusion: Clinicians need to elicit the individual perceptions of PA within the individual disease context for PwSLE to ensure balance of the inductive and deductive themes in order to facilitate manageable PA. SLE is a conglomerate disease, which requires a sensitive and tailored approach to ensure PwSLE are assisted to control their disease while optimising PA levels, an infographic (figure 2 ) has been constructed to use as a prompt for clinicians. Acknowledgements: We thank NIHR for providing funding for this masters project. We also thank Lupus UK for providing feedback on study documents and developing the interview topic guide. We thank the patients at the Lupus Centre patient forum for engaging with the project and finally all of the recruits for taking part. Funding: Chloe Keith-Jopp was funded by a National Institute for Health Research (NIHR), Masters in Clinical Research grant for this research project. This manuscript represents independent research funded by the National Institute for Health Research (NIHR). The views expressed are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health and Social Care.